FRANCE’S POLICY TOWARDS UKRAINE IN THE CONTEXT OF THE UKRAINIAN – RUSSIAN WAR - Денисенко , К.Ю.; Ковтун , Е.Ю.; Ковтун , О.Ю. (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2021)
Abstract. The article discusses the influence and the risks from France’s rapprochement with the Russian Federation in the aftermath of Ukrainian – Russian war, what can present a threat to the EU Neighborhood Policy. The ideas and views expressed in the article, present exclusively the point of view of authors, who relied on a wide range of documents and official information from open sources, but they do not necessarily have to coincide with the opinion of other specialists. Currently expressing the desire to get Russia back to the dialogue with the European Union, which throughout the history defined Moscow as one of the main economic partners, France pursues the policy of appeasing the aggressor, neglecting the war in Ukraine. The Russian Federation violated the basics of the international law, having annexed the Crimean Peninsula and having occupied certain areas of Donetsk and Lugansk regions. The article underlines that Ukraine is not alone in the long least of Moscow pro-imperial plans and presents a threat to the stability and security of the continent. The analyses, also demonstrates the politics of France towards Ukraine during the last seven years. The article provides a complex evidence that there is a connotation between the Ukrainian – Russian war and the desire of Moscow to establish the instability zone along the borders of the European Union.Keywords: France, Russia, Ukraine, bilateral relations, conflict resolution.

Аннотация. В статье рассматривается влияние и риски сближения Франции с Российской Федерацией в контексте украинско-российской войны, что может представлять угрозу политике соседства ЕС. Идеи и взгляды, изложенные в статье, представляют исключительно точку зрения авторов, опиравшихся на широкий спектр документов и официальной информации из открытых источников, но они не обязательно должны совпадать с мнением других исследователей. Выражая желание вернуть Россию к диалогу с Европейским Союзом, Франция, которая на протяжении всей истории определяла Москву одним из главных своих экономических партнеров, проводит политику умиротворения агрессора, пренебрегая войной в Украине. Российская Федерация нарушила основы международного права, аннексировав Крымский полуостров и оккупировав отдельные районы Донецкой и Луганской областей. В статье подчеркивается, что Украина не является последним пунктом в проимперских планах Москвы и представляет непосредственную угрозу стабильности и безопасности континента. Исследование также показывает политику Франции в отношении Украины за последние семь лет. В статье приводятся доказательства, что существует прямая связь между украинско-российской войной и желанием Москвы создать зону нестабильности вдоль границ Европейского Союза. Ключевые слова. Франция, Россия, Украина, двусторонние отношения, разрешение конфликтов.

Анотація. У статті розглядається вплив та ризики зближення Франції з Російською Федерацією у контексті українсько-російської війни, що може становити загрозу для політики сусідства ЄС. Ідеї та погляди, викладені в статті, представляють виключно точку зору авторів, які спиралися на широкий спектр документів та офіційної інформації з відкритих джерел, але вони не обов’язково повинні збігатися з думкою інших дослідників. Висловлюючи бажання повернути Росію до діалогу з Європейським Союзом, Франція яка протягом усієї історії визначала Москву одним із головних своїх економічних партнерів, проводить політику умиротворення агресора, нехтуючи війною в Україні. Російська Федерація порушила основи міжнародного права, анексувавши Кримський півострів та окупувавши окремі райони Донецької та Луганської областей. У статті підкреслюється, що Україна не є останнім пунктом у проімперських планах Москви і вона становить безпосередню загрозу стабільності та безпеці континенту. Дослідження також показує політику Франції щодо України протягом останніх семи років. У статті наводяться докази того, що існує прямий зв'язок між українсько-російською війною та бажанням Москви створити зону нестабільності вздовж кордонів Європейського Союзу. Ключові слова. Франція, Росія, Україна, двосторонні відносини, вирішення конфліктів.
ПОЛИТИКА ФРАНЦИИ ПО ОТНОШЕНИЮ К УКРАИНЕ В КОНТЕКСТЕ УКРАИНСКО – РОССИЙСКОЙ ВОЙНЫ
ПОЛІТИКА ФРАНЦІЇ ЩОДО УКРАЇНИ У КОНТЕКСТІ УКРАЇНСЬКО – РОСІЙСЬКОЇ ВІЙНИ